Study on the Division of the Affected Zone under Construction Unloading and Its Construction Sequence of the Multiline Parallel River-Crossing Pipe Jacking - Zhang Ziguang; Mao Ruijin; Zhang Jiesheng; Wang Xuefeng; Zhang Mengqing (Advances in Civil Engineering)
There are many advantages of reasonably determining the affected zone and its construction sequence for the multiline parallel pipe-jacking construction, such as convenient to reasonably arrange the pipeline section distribution mode, reducing the construction safety risk, and construction difficulty. Combined with the engineering construction practice of the multiline parallel pipe-jacking project for the north city drainage and flood control project through Chu River in Hefei, the strength reduction method has been utilized to study the surrounding stratum FOS for the pipe-jacking construction unloading under different overburden thickness Hs, different clear distance D, and different river water depth Hw in this paper. The formula of the minimum critical overburden thickness Hsmin and the minimum critical clear distance Dmin of the surrounding stratum self-stability during pipe-jacking construction unloading have been derived. The division method of the affected zone for the multiline parallel river-crossing pipe-jacking construction which behaves as the mutual influence nonself-stability zone, the mutual influence self-stability zone, and the no mutual influence self-stability zone has been proposed. For further discussion, the construction sequence of the multiline parallel river-crossing pipe jacking has been studied.